Immunogenicity of SARS inactivated vaccine in BALB/c mice - Xiong, Sheng (Immunol Lett, 2004)
Severe acute respiratory syndrome (SARS) is a serious infectious threat to public health. To create a novel trial vaccine and evaluate its potency, we attempted to generate a SARS inactivated vaccine using SARS coronavirus (SARS-CoV) strain F69 treated with formaldehyde and mixed with Al(OH)(3). Three doses of the vaccine were used to challenge three groups of BALB/c mice. We found that the mice exhibited specific IgM on day 4 and IgG on day 8. The peak titers of IgG were at day 47 in low-dose group (1:19,200) and high-dose group (1:38,400) whereas in middle-dose group (1:19,200), the peak was at day 40. On day 63, the IgG levels reached a plateau. Neutralization assay demonstrated that the antisera could protect Vero-E6 cells from SARS-CoV's infection. Analysis of the antibody specificity revealed that the mouse antisera contained a mixture of antibodies specifically against the structure proteins of SARS-CoV. Furthermore, the mouse antisera conferred higher amount of antibodies against protein N, polypeptide S4 and S2 than those of proteins M and 3CL. These findings suggest that the inactivated SARS-CoV could preserve its antigenicity and the inactivated vaccine can stimulate mice to produce high levels of antibodies with neutralization activity. Results also suggest that polypeptides originating from protein N or S might be a potential target for the generation of a recombinant SARS vaccine.